Anti-biofilm and anti-adherence activities of sub fraction 18 of melastoma malabathricum towards streptococcus mutans - Rohazila M.H.; Nazlina I.; Yaacob W.A. (American Institute of Physics Inc., 2024)
Indexed by Scopus